The relationship between corporate social responsibility and employee commitment in MCS College Banting / Nurfaizahana Abdul Razak - Abdul Razak, Nurfaizahana (Faculty of Business and Management, 2018)
This study was carried out to identify the factors that influence Corporate Social Responsibility (CSR) and Employee Commitment in MCS College, Banting. In chapter one, the researcher discussed about the background of the study. This research is to study about the activities in CSR as the independent variables (IV) toward the employee commitment as the dependent variable (DV). The objective of this study are to identify the level of awareness of Corporate Social Responsibility (CSR) and Employee Commitment among employees in the organization and to determine the relationship between Corporate Social Responsibility (CSR) and the Employee Commitment in the organization. As explained chapter three, methodology use for this research has been discussed. The methodology is the method used by the researcher in finding the result while completing this research. This is including research design, sampling frame, population, sampling technique and sample size, unit of analysis, instrument and validity of instrument, data collection procedure and plan of data analysis. The researcher use simple random sampling technique. The scope of the study only revolves within the organization and chosen worker from the selected department as the respondents for this research. The researcher has chosen workers from Academic Department in MCS College, Banting for this study. About 52 set of questionnaires with 21 questions were distributed the respondents to the study. The data collected was evaluated by using SPSS software to find the result between the variables. The finding are discussed in chapter 4. For the conclusion and recommendation have been discussed in chapter five.